REPRESENTASI AGEISME DALAM FILM THE SUBSTANCE - Nuzulan Rohadatul Aisy; Hapsari Dwiningtyas Sulistyani (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2026)
This study examines the representation of ageism in The Substance. The film was selected because it highlights women’s aging as an issue of the body, identity, and social value. The study aims to understand how ageism toward women is constructed through the age standards portrayed in the film and how these practices are interpreted and represented through the depiction of young and aging bodies. Employing a critical paradigm and a qualitative descriptive approach, the study analyzes data using John Fiske’s semiotic model through the levels of reality, representation, and ideology. The data consist of fifteen selected scenes containing signs related to young bodies, aging bodies, age discrimination, and the social standards imposed on women. The findings reveal that ageism toward women is constructed through age standards shaped by the entertainment industry, which is embedded in patriarchal culture and capitalism, where women’s value is determined by age, physical attractiveness, and the ability to conform to dominant visual standards. Consequently, aging women are positioned as bodies that have lost their relevance and social value. Furthermore, age discrimination is represented through the opposition between young and aging bodies. Young bodies are portrayed as ideal bodies that receive acceptance, validation, and social visibility, whereas aging bodies are associated with alienation, loss of attractiveness, and diminished self worth. The film also illustrates how these standards become internalized by the main character, as the young body is perceived as the ideal self, while the aging body is regarded as shameful and something to be eliminated. The pressure to maintain youthfulness ultimately develops into symbolic and physical violence against women. Through its body horror aesthetics, the film demonstrates that ageism against women is a structural issue closely related to patriarchy, the capitalist entertainment industry, and beauty standards that position youthfulness as a source of women’s social value. Although the film presents a critique of ageism, at the ideological level it ultimately reinforces the dominant discourse that glorifies women’s youthful bodies while marginalizing aging as a condition associated with the loss of social value.